2011
DOI: 10.1186/1747-597x-6-33
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, distribution and correlates of tobacco smoking and chewing in Nepal: a secondary data analysis of Nepal Demographic and Health Survey-2006

Abstract: BackgroundNearly four-fifths of estimated 1.1 million smokers live in low or middle-income countries. We aimed to provide national estimates for Nepal on tobacco use prevalence, its distribution across demographic, socio-economic and spatial variables and correlates of tobacco use.MethodsA secondary data analysis of 2006 Nepal Demographic and Health Survey (DHS) was done. A representative sample of 9,036 households was selected by two-stage stratified, probability proportional to size (PPS) technique. We const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
65
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(85 citation statements)
references
References 19 publications
18
65
1
Order By: Relevance
“…In our study, the prevalence of current tobacco consumption was 37.5% which was higher than the study done among Nepali medical students 22% and in Patna 12.5%. Our study result was similar to the nationwide survey done in 2006 by Sreeramareddy et al, 8 which showed the prevalence of tobacco consumption was 30.3%. Smoking and tobacco consumption were significantly high in male population (64.3 vs 6.7) in overall as well as among all age groups in our study.…”
Section: Discussionsupporting
confidence: 81%
“…In our study, the prevalence of current tobacco consumption was 37.5% which was higher than the study done among Nepali medical students 22% and in Patna 12.5%. Our study result was similar to the nationwide survey done in 2006 by Sreeramareddy et al, 8 which showed the prevalence of tobacco consumption was 30.3%. Smoking and tobacco consumption were significantly high in male population (64.3 vs 6.7) in overall as well as among all age groups in our study.…”
Section: Discussionsupporting
confidence: 81%
“…9 The rural nature of this community may be the reason for the high prevalence of smokeless tobacco use and showed why more than half of the respondents have been using smokeless tobacco for 6-10 years and greater than thrice daily frequency was reported by more than three-quarters (77.3%) of the respondents. Reports have shown higher smokeless tobacco use in rural areas [17][18][19] and mountainous areas. 19 Tobacco use contributes to higher malnutrition and illiteracy rates, since money that could have been used for food and education is spent on tobacco.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have shown higher smokeless tobacco use in rural areas [17][18][19] and mountainous areas. 19 Tobacco use contributes to higher malnutrition and illiteracy rates, since money that could have been used for food and education is spent on tobacco. 5 In this study, the smokeless tobacco use was more among those aged 50-59 years.…”
Section: Discussionmentioning
confidence: 99%
“…Nepal also has a very high prevalence rate of chronic obstructive lung disease (COLD) varying from 20-40% in persons above the age of twenty years which was found to be significantly associated with tobacco smoking. 20,21 Near about forty percent (38.9%) health worker had faced social problems in their working area.…”
Section: Discussionmentioning
confidence: 99%